Concurrent Objects and Beyond Papers dedicated to Akinori Yonezawa on the Occasion of His 65th Birthday - Agha, Gul.; Igarashi, Atsushi; Kobayashi, Naoki; Masuhara, Hidehiko; Matsuoka, Satoshi; Shibayama, Etsuya; Taura, Kenjiro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This Festschrift volume includes a collection of papers written in honor of the accomplishments of Professor Yonezawa on the occasion of his 65th birthday in 2012. With a few exceptions, the papers in this Festschrift were presented at an international symposium celebrating this occasion. Also included are reprints of two of Professor Yonezawa's most influential papers on the programming language ABCL. The volume is a testament strong and lasting impact Professor Yonezawa's research accomplishments as well as the inspiration he has been to colleagues and students alike.
My Early Education and Concurrent Objects -- Object-Oriented Concurrent Programming in ABCL/1 -- Reflection in an Object-Oriented Concurrent Language -- Building Safe Concurrency Abstractions -- Structuring Communication with Session Types -- From Linear Types to Behavioral Types and Model Checking -- SALSA Lite: A Hash-Based Actor Runtime for Efficient Local Concurrency -- Past and Future Directions for Concurrent Task Scheduling -- Controlling Concurrency and Expressing Synchronization in Charm++ Programs -- MassiveThreads: A Thread Library for High Productivity Languages -- On Efficient Load Balancing for Irregular Applications -- Verifiable Object-Oriented Transactions -- Design and Implementation of a Mobile Actor Platform for Wireless Sensor Networks -- Objects in Space -- Towards a Substrate Framework of Computation -- Event-Based Modularization of Reactive Systems -- From Actors and Concurrent Objects to Agent-Oriented Programming in simpAL.
Keywords: Computer science; Computer programming; Software engineering; Programming languages (Electronic computers).; Operating systems (Computers).; Computers; Computer Science; Software Engineering; Computing Methodologies; Programming Languages, Compilers, Interpreters; Operating Systems; Programming Techniques; Electronic books